Die boek Prediker: Alles is nie sinloos nie! - Steyn, J. J. (Verbum et ecclesia, 2000)
Ecclesiastes: Everything is not meaningless! Ecclesiastes is not dominated by the statement of meaningless, but also provides positive advice. The majesty and glory of God and his sovereignity, reflects one of the main themes in this book. God rules man’s destiny, his/her successes and happiness. Man’s attitude can best be summarized in the following words from Ecclesiastes 12:13: "Fear God and keep his commandments". Ecclesiastes continuously emphasizes the great value of wisdom. This can be attributed to the fact that God Himself is the author of wisdom. However, wisdom also has limits. Even with all man's wisdom, she/he is still limited, as even wise people can not explain all that happens on earth. Ecclesiastes does not only become meaningfull when looking at the New Testament, it has its own message for today's Christians.